Pemanfaatan Literacy Cloud Berbasis Google Clasroom untuk Meningkatkan Literasi Membaca Murid di Masa Pandemi - Walan Yudiani (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The aim of this research is to find out whether cloud literacy based on Google Classroom can improve the reading literacy of students at SDN Pejaten Timur 01. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles. Data collection was carried out using questionnaires, written test techniques and documentation. The collected data was processed descriptively qualitatively and quantitatively. The results of research at cognitive level 1, 29 students in class 5D (93.55%) were able to find and retrieve explicit information in the text and make simple interpretations and 6.45% (2 people) were not able. At cognitive level 2, as many as 28 people (90.32%) were able to make interpretations of the implicit information in the text; make conclusions from the results of integrating several pieces of information in a text, and as many as 3 people (9.68%) were not able to. At level 3, only 13 (41.94%) class 5D students were able to integrate some information across texts; evaluate the content, quality, method of writing a text, and be reflective about the content of the text; the remaining 58.06% (18 students) are not yet capable. The results of the student questionnaire showed that the use of literacy cloud as a reading literacy medium during the pandemic was acceptable.